Arrest of children in conflict with the law; a comparative analysis between malaysian law and the international standards - Aminuddin, Mustaffa; Nazli, Ismail@Nawang; Mohd Badrol, Awang; Mohd Lotpi, Mohd Yusob (2017)
Arrest is one of the most important issues as far as the juvenile justice system is concerned. Generally, the law permits the police to arrest children for the purpose of investigation. While the arrest process undeniably aims to maintain public order and justice, it may turn out to be a terrifying event for children, who are known for their physical and emotional vulnerability. This paper aims to comparatively analyse between Malaysian current law and practice on arrest of children and the international standards set by the international instruments. It attempts to examine to what extent current Malaysian law on arrest measure up with the requirements of international standards and accordingly proposes recommendations for possible legal reform on this aspect of law.